Fandango [videorecording (DVD)] - Zinnemann, Tim; Reynolds, Kevin, 1952-; Costner, Kevin; Nelson, Judd; Robards, Sam; Bush, Chuck, 1961-; Cesak, Brian; McIntyre, Marvin J.; Amis, Suzy (Warner Home Video, 2005)
Five college pals, graduating in 1971, have one last fling before moving on to face life.